MIMO OFDM Radar-Communication System with Mutual Interference Cancellation - Sit, Yoke Leen (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2017)
This work describes the OFDM-based MIMO Radar-Communication System, intended for operation in a multiple-user network, especially the automotive sector in the vehicle-to vehicle/infrastructure network. The OFDM signals however are weak towards frequency offsets causing subcarrier misalignment and corrupts the radar estimation and the demodulation of the communication signal. A simple yet effective interference cancellation algorithm is detailed here with real time measurement verification.